Enrichment and Aggregation of Purple Non-sulfur Bacteria in a Mixed-Culture Sequencing-Batch Photobioreactor for Biological Nutrient Removal From Wastewater - Cerruti, Marta; Stevens, Berber; Ebrahimi, Sirous; Alloul, Abbas; Vlaeminck, Siegfried E.; Weissbrodt, David G. (Frontiers in Bioengineering and Biotechnology, 2020)
Mixed-culture biotechnologies are widely used to capture nutrients from wastewater. Purple non-sulfur bacteria (PNSB), a guild of anoxygenic photomixotrophic organisms, rise interest for their ability to directly assimilate nutrients in the biomass. One challenge targets the aggregation and accumulation of PNSB biomass to separate it from the treated water. Our aim was to enrich and produce a concentrated, fast-settling PNSB biomass with high nutrient removal capacity in a 1.5-L, stirred-tank, anaerobic sequencing-batch photobioreactor (SBR). PNSB were rapidly enriched after inoculation with activated sludge at 0.1 gVSS L-1 in a first batch of 24 h under continuous irradiance of infrared (IR) light (>700 nm) at 375 W m-2, with Rhodobacter reaching 54% of amplicon sequencing read counts. SBR operations with decreasing hydraulic retention times (48 to 16 h, i.e., 1 to 3 cycles d-1) and increasing volumetric organic loading rates (0.2 to 1.3 kg COD d-1 m-3) stimulated biomass aggregation, settling, and accumulation in the system, reaching as high as 3.8 g VSS L-1. The sludge retention time (SRT) increased freely from 2.5 to 11 d. Acetate, ammonium, and orthophosphate were removed up to 96% at a rate of 1.1 kg COD d-1 m-3, 77% at 113 g N d-1 m-3, and 73% at 15 g P d-1 m-3, respectively, with COD:N:P assimilation ratio of 100:6.7:0.9 m/m/m. SBR regime shifts sequentially selected for Rhodobacter (90%) under shorter SRT and non-limiting concentration of acetate during reaction phases, for Rhodopseudomonas (70%) under longer SRT and acetate limitation during reaction, and Blastochloris (10%) under higher biomass concentrations, underlying competition for substrate and photons in the PNSB guild. With SBR operations we produced a fast-settling biomass, highly (>90%) enriched in PNSB. A high nutrient removal was achieved by biomass assimilation, reaching the European nutrient discharge limits. We opened further insights on the microbial ecology of PNSB-based processes for water resource recovery.